English Children Literature for Exploring Immigrant Identity in a Language Classroom - Jariya Sairattanain; Thiwaporn Thawarom (Universitas Negeri Makassar, 2022)
The purpose of this article is to propose a possible way to integrate cultural knowledge into English teaching by using children literature. It also presents an alternative method for researchers to investigate personal identity by using a character from literature as a case study. The article also offers an example of an exploration of the main characters’ identity in Jasmin Warga’s Other Words for Home. The story represented a life of a twelve-year-old girl from Syria who left behind the war torn city order to live in United States. Her identity formation process was analyzed through the theory of Symbolic Interactionism. Themes found from her journey of moving into new culture included “self as an English language learner” prior to moving to the United States and “self as an immigrant” was presented when she entered American society. her This teaching method might be useful in promoting English learners to become integratively motivated which can be achieved by understanding the cultural and ideological aspects and by developing a cross-cultural awareness of the how to become part of community that speak the target language.